THE EFFECT OF PYROLYSIS TEMPERATURE ON THE HEAT VALUE OF PYRO-OIL USING PLASTIC WASTE - I Made Agus Putrawan (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
This work primarily investigated the pyrolysis of smalls scale fixed bed reactor using plastic wastes type LDPE during slow pyrolysis (non-isothermal) in a batch reactor to assess the effect of different temperatures on the product yield and heating value. The calorie bomb of Parr Instrument was performed to investigated heating value of pyro-oil product at different temperatures 250, 275, 300oC. The pyro-oil obtained at higher product yield of 300 oC while the increased temperature will affect to increase the product yield of pyro-oil. The highest heating value of pyro-oil produced at a reactor temperature of 300oC is 9,769.78 cal/gr. From the results of pyro-oil using plastic waste type LDPE, the characteristics of the heating value are equivalent to diesel fuel.